EKSPLORASI KETERLIBATAN OSIS DALAM MEMBENTUK KARAKTER KEPEMIMPINAN SISWA DI SMAN 1 ANGGANA - Nur Ulandari, Melda; Asnar, Asnar; Hardoko , Aloysius; Suryaningsih, Suryaningsi (Universitas Negeri Medan, 2025)
Abstract: This study aims to explore how student involvement in the OSIS (Intra-School Student Organization) at SMA 1 Anggana, East Kalimantan, contributes to the development of leadership character through organizational experience. Using a qualitative phenomenological approach, data were collected through in-depth interviews with eight informants, including the OSIS president, core administrators, active members, and the supervising teacher. The main instrument was a semi-structured interview guide. Data analysis followed the Miles and Huberman model, involving data reduction, presentation, and verification. The findings reveal that active involvement in OSIS significantly shapes students’ leadership character, particularly in terms of responsibility, discipline, decision-making, and self-confidence. These results emphasize the vital role of student organizations as a platform for leadership character education in secondary schools Keyword: Student Involvement, Student Leadership, Character Development, Organizational Experience, Secondary School Abstrak: Penelitian ini bertujuan mengungkap bagaimana keterlibatan siswa dalam OSIS di SMA 1 Anggana, Kalimantan Timur, membentuk karakter kepemimpinan mereka melalui pengalaman berorganisasi. Menggunakan pendekatan kualitatif fenomenologis, data dikumpulkan melalui wawancara mendalam terhadap delapan informan, terdiri dari ketua, pengurus inti, anggota aktif OSIS, dan pembina. Instrumen penelitian berupa pedoman wawancara semi-terstruktur. Analisis data dilakukan dengan model Miles dan Huberman melalui proses reduksi, penyajian, dan verifikasi data. Hasil penelitian menunjukkan bahwa keterlibatan dalam OSIS secara signifikan membentuk karakter kepemimpinan siswa, terutama pada aspek tanggung jawab, disiplin, pengambilan keputusan, dan kepercayaan diri. Temuan ini menegaskan pentingnya organisasi siswa sebagai media pembelajaran karakter kepemimpinan di sekolah. Kata Kunci: Keterlibatan OSIS, Kepemimpinan Siswa, Karakter, Pengalaman Organisasi, Sekolah Menengah